EFFECT OF SIDA CORDIFOLIA LINN. LEAF AND ROOT ETHYL ACETATE EXTRACTS ON THE GROWTH AND PHYSIOLOGICAL RESPONSE OF PANICUM REPENS AND PANICUM MAXIMUM - SAMBO, G.Y; CHIA, M.A; IORTSUUN, D.N; AMAPU, I.Y (FUDMA Journal of Earth and Environmental Sciences, 2024)
Due to the incessant application of synthetic herbicides in the agricultural system coupled with a rapid increase in herbicide-resistant weed species across the globe, much attention has been focused on alternative weed management, including allelopathy, which is eco-friendly and reduces reliance on synthetic herbicides. The effect of Sida cordifolia root and leaf ethyl acetate extract was evaluated under field conditions to determine its effects on growth, physiological response, stomatal index and density, and biochemical activity on weed species (Panicum maximum, Panicum repens, and Andropogon gayanus), as well as its effects on soil micronutrients. S. cordifolia root and leaf were collected from the wild in Nigeria and prepared into powder, which was dissolved to obtain the following concentrations 10, 20, 40, 60, and 80%, and distilled water served as the control. The percentage inhibition seems to be correlated with different growth indices as proven by an increase in malondialdehyde (MDA) content, reactive oxygen species (ROS), glutathione transferase (GST), and peroxidase (POD). Physiological growth indices such as plant height, leaf area, number of leaves, dry weight, stomatal density, and stomatal index were inhibited in both weed species while biochemical parameters such as Chlorophyll a, b, total chlorophyll and chlorophyll stability index were slightly reduced, increase in MDA, GST, ROS and POD were also noticed. In general, Andropogon gayanus showed a high inhibition rate compared to tomato. It is therefore recommended that concentrations of the Sida cordifolia extracts be increased to have a robust effect on the physiological processes of the weed species.